THE IMPACT OF PROACTIVE WORK BEHAVIOR ON ORGANIZATIONAL PERFORMANCE MEDIATED BY ORGANIZATIONAL FLEXIBILITY : An analytical study of the opinions of a sample of employees at Al-Kut Private College in Wasit Governorate - Dhahi, Kareem Jaber (DYNAMICS: Journal of Public Administration, 2024)
This study aims to know the proactive behavior that is circulated by private universities and the extent of its impact in its dimensions (bearing responsibilities, worker voice, worker creativity, recognizing problems) on organizational performance in its dimensions (economic performance, social performance, environmental performance) through innovation as an intervening variable in its dimensions (structural flexibility, yuan, six strategic) as the study was conducted on the deanship workers in (Kut University College) as the problem of the extended research stems from the weakness of the workers organizationally and there must be a solution to this problem, so the questionnaire was used as a primary tool in collecting confirmed data about the technical study, and a recent study was represented in ((248 from a community numbering (702) and based on the table that was successful by Morcan, which shows the appropriate sample size for each community, ((248 were distributed, of which (217) were retrieved, i.e. (13) were not retrieved, and (18) were not valid for analysis. The analysis and testing of hypotheses were conducted using the program (SPSS V.20), ( PLS SMART), where the sample is determined (all employees in Al-Kut Private College in Wasit Governorate) as it was represented by the following departments (Dentistry, Education, Engineering Technologies, Medical Physics Sciences, Pharmacy, Medical Laboratory Technologies, Laser Engineering and Optoelectronics, Anesthesia Technologies, Electrical Power Technology Engineering, Business Administration, Arabic Language, Quranic Sciences, Nursing, English Language, Chemical Engineering and Petroleum Refining, Law, Efficiently), but the implementation performed by knowledge was the completeness of the descriptive analysis.